Indoor heat stress: An assessment of human bioclimate using the UTCI in different buildings in Berlin - Langner, Marcel; Scherber, Katharina; Endlicher, Wilfried R. (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
Because humans spend most of their time indoors and can be negatively affected by unfavourable thermal environments, the assessment of indoor heat stress is an important issue for public health care. To characterise indoor human bioclimate, the Universal Thermal Climate Index (UTCI) was used. UTCI values were calculated from measurements of air temperature and air humidity in 16 rooms in Berlin during the summer months of 2011 and 2012. A constant air velocity of approximately 0.3 m/s and a metabolic heat production of 135 W/m2 were assumed. The mean radiant temperature was set to the air temperature. Because the mean air humidity was below or slightly above 50 %, the calculated UTCI values were mostly lower than the air temperatures. In summer 2012, the mean UTCI values ranged from 22.2 °C to 27.1 °C, and the maximum UTCI values ranged from 24.7 °C to 35.6 °C. Whereas only minor differences were found between rooms located within comparable buildings in different districts of Berlin, pronounced variations of the UTCI values were detected in two adjoining buildings, with differences up to 8.6 K for the daily minimum, 9.8 K for the daily mean and 12.2 K for the daily maximum UTCI between different rooms. These variations can be explained by differences in the structures of the two buildings, floor level and aspect. The UTCI values were also used to determine the occurrence of moderate and strong heat stress. Only two rooms showed no thermal stress, while strong heat stress was detected in three rooms.